2017
DOI: 10.1111/jsap.12691
|View full text |Cite
|
Sign up to set email alerts
|

Owner assessment of the outcome of tibial plateau levelling osteotomy without meniscal evaluation for treatment of naturally occurring cranial cruciate ligament rupture: 130 cases (2009 to 2013)

Abstract: Considering the low incidence of persistent lameness after surgery and the limits of diagnosis and treatment, the need for routine meniscal examination during tibial plateau levelling osteotomy is questionable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…Study duration varied from 3 days ( 37 ) up to 5 years ( 58 , 60 64 ). Twenty-eight, 26 and 18 studies evaluated mid-term, short-term and long-term outcomes, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study duration varied from 3 days ( 37 ) up to 5 years ( 58 , 60 64 ). Twenty-eight, 26 and 18 studies evaluated mid-term, short-term and long-term outcomes, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies (51.4 %) deliver an unclear risk of bias as they did not correctly report every detail concerning study design and outcome data. Unclear or high risk of bias was also seen in studies ( 54 , 56 , 60 64 , 68 , 70 77 ) that were (partly) based on results stated by the owners or referring vets ( Table 1 ). These might not have followed standard protocols, but be influenced by the owners' or referring vets' personal opinion and bias toward the treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cases 4, 5 and 6 were not investigated for meniscal tears because of surgeon preference. In the veterinary literature there is still lack of evidence regarding the outcome of untreated meniscal injuries [21]. Since it has been anecdotally reported that clinical function following meniscal injury may improve in the absence of meniscal intervention, it is possible that the improvement in clinical function of these patients was secondary to spontaneous remission of a meniscal injury rather than to the TPLO performed.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment outcome in dogs with CCLD has been evaluated in several ways, for example, by using force plate gait analysis, visual gait observation, orthopaedic and physiotherapeutic examination, radiography for evaluation of OA progression and owner questionnaires 8,17,22–29 . Owner questionnaires based on behaviour are considered one of the most reliable tools for assessment of chronic pain in dogs 30–32 .…”
Section: Introductionmentioning
confidence: 99%